Interjection Bah! in Batak Toba: A natural semantic metalanguage approach - Bertova Simanihuruk; Mulyadi Mulyadi (Studies in English Language and Education, 2020)
Interjection is the word used to show spontaneous expression. Batak language has a specific emotive interjection Bah! which is different from other interjections in the language. The objectives of this study are to find the meanings of interjection Bah! and to classify the elements of feelings of this interjection. This is a descriptive qualitative study employing the semantic explication method of the Natural Semantic Metalanguage approach. The data was collected from the interjection Bah! in a Batak Toba short story entitled Mangongkal Holi. The data were obtained by the attentive observation method and tapping technique. The methods used for data analysis were the distribution and contextual method. The results of this study showed that there are five meanings of the interjection Bah! They are astonishment, disappointment, confusion, surprise, and amazement. Meanwhile, those meanings express two elements of feelings, which are the positive feeling element (i.e. surprise and amazement), and the negative feeling element (i.e. astonishment, disappointment, and confusion). The revelation of the various meanings of Bah! is expected to provide richer understanding on its use in communication, and to further avoid miscommunication between different ethnics in Indonesia which each has their own mother tongue.